Clinical metagenomic identification of Balamuthia mandrillaris encephalitis and assembly of the draft genome: the continuing case for reference genome sequencing. Issue 1 (December 2015) - Greninger, Alexander; Messacar, Kevin; Dunnebacke, Thelma; Naccache, Samia; Federman, Scot; Bouquet, Jerome; Mirsky, David; Nomura, Yosuke; Yagi, Shigeo; Glaser, Carol; Vollmer, Michael; Press, Craig; et al.
Abstract Background Primary amoebic meningoencephalitis (PAM) is a rare, often lethal, cause of encephalitis, for which early diagnosis and prompt initiation of combination antimicrobials may improve clinical outcomes. Methods In this study, we sequenced a full draft assembly of theBalamuthia mandrillaris genome (44.2 Mb in size) from a rare survivor of PAM, and recovered the mitochondrial genome from six additionalBalamuthia strains. We also used unbiased metagenomic next-generation sequencing (NGS) and SURPI bioinformatics analysis to diagnose an ultimately fatal case ofBalamuthia mandrillaris encephalitis in a 15-year-old girl. Results and Discussion Comparative analysis of the mitochondrial genome and high-copy number genes from six additionalBalamuthia mandrillaris strains demonstrated remarkable sequence variation, and the closestBalamuthia homologs corresponded to other amoebae, hydroids, algae, slime molds, and peat moss. Real-time NGS testing of hospital day 6 CSF and brain biopsy samples detectedBalamuthia on the basis of high-quality hits to 16S and 18S ribosomal RNA sequences present in the National Center for Biotechnology Information (NCBI) nt reference database. The presumptive diagnosis of PAM by visualization of amoebae on brain biopsy histopathology and NGS analysis was subsequently confirmed at the US Centers for Disease Control and Prevention (CDC) using aBalamuthia -specific PCR assay. Retrospective analysis of a day 1 CSF sample revealed that more timely identification ofBalamuthia by metagenomic NGS, potentially resulting in a better clinical outcome, would have required availability of the complete genome sequence. Conclusions These results underscore the diverse evolutionary origins ofBalamuthia mandrillaris, provide new targets for diagnostic assay development, and will facilitate further investigations of the biology and pathogenesis of this eukaryotic pathogen. The failure to identify PAM from a day 1 sample without a fully sequencedBalamuthia genome in the database highlights the critical importance of whole-genome reference sequences for microbial detection by metagenomic NGS.